Think new syallabus mathematics book 2 . - Ban Har, Yeap. (Karachi : Oxford university press, 2024)
Think !!!New Syllabus Mathematics is a series designed to foster both a deep understanding and appreciation of mathematics .Book typically focuses on equations and functions.
Keywords: Oxford mathematics book; Mathematics book 2.